2021
DOI: 10.1002/clc.23723
|View full text |Cite
|
Sign up to set email alerts
|

Plasma catecholamine levels in the acute and subacute stages of takotsubo syndrome: Results from the Stockholm myocardial infarction with normal coronaries 2 study

Abstract: Aims: It is well-accepted that takotsubo syndrome (TS) is characterized by a massive surge of plasma catecholamines despite lack of solid evidence. The objective of this study was to examine the hypothesis of a massive catecholamine elevation in TS by studying plasma-free catecholamine metabolites in patients participating in the Stockholm myocardial infarction (MI) with normal coronaries 2 (SMINC-2) study where TS constituted more than one third of the patients. Methods and results:The patients included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Ali study found that phosphodiesterase inhibitors (milrinone) can also cause TTC-like changes in cardiac function without exogenous catecholamines, 29 and Y-Hassan study found that circulating catecholamines are not the cause of TTC, as most patients with TTC have normal catecholamine metabolites. 30 It is still unclear how stress affects cardiomyopathy because it is not an instantaneous event but can last for a while. In We demonstrated that cardiac dysfunction might emerge after 1 day of IMO stress and could continue as the duration of stress without recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ali study found that phosphodiesterase inhibitors (milrinone) can also cause TTC-like changes in cardiac function without exogenous catecholamines, 29 and Y-Hassan study found that circulating catecholamines are not the cause of TTC, as most patients with TTC have normal catecholamine metabolites. 30 It is still unclear how stress affects cardiomyopathy because it is not an instantaneous event but can last for a while. In We demonstrated that cardiac dysfunction might emerge after 1 day of IMO stress and could continue as the duration of stress without recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Isoprenaline injections are currently being used in animal studies to create a model of TTC, and the severe cardiac dysfunction that manifests in this model is thought to be caused by acute drug toxicity rather than the pathological mechanism of TTC itself. Ali study found that phosphodiesterase inhibitors (milrinone) can also cause TTC‐like changes in cardiac function without exogenous catecholamines, 29 and Y‐Hassan study found that circulating catecholamines are not the cause of TTC, as most patients with TTC have normal catecholamine metabolites 30 . It is still unclear how stress affects cardiomyopathy because it is not an instantaneous event but can last for a while.…”
Section: Discussionmentioning
confidence: 99%
“…It is stated in the literature that the increased concentration of catecholamines caused by emotional or physical stress causes coronary vasospasm and microcirculation abnormalities, which may be one of the explanations for the development of TCM [ 10 , 11 ]. However, the SMINC-2 trial, which included patients with Takostubo cardiomyopathy, showed no evidence of massive catecholamine elevations [ 12 ]. Somatic stressors include intracranial events, severe infections, and surgical trauma [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…140 In another study, 38 (86.4%) of the 44 patients with TTS had totally normal plasma metanephrine and normetanephrine levels; 5 (11.6%) of the 43 patients with TTS had mild increases (∼1.2 times the upper normal limits) of either plasma metanephrine or normetanephrine; 1 patient with pheochromocytoma-induced TTS had excessive increase of plasma metanephrine and mild increase of plasma normetanephrine. 141 The authors concluded that they did not find huge catecholamine increases in the acute and subacute phases of TTS except for one patient with pheochromocytoma-related TTS; most of the TTS patients had normal catecholamine metabolites suggesting that circulating catecholamines may not have a direct effect in the pathogenesis of TTS. However, the sympathetic activation and surge with norepinephrine released topically from sympathetic nerve terminals has been considered to play a critical role in the acute phase of TTS.…”
Section: Pro-arrhythmic Mechanismsmentioning
confidence: 93%